2012
DOI: 10.1159/000342228
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Microparticles: Clinical Relevance

Abstract: Microparticles are small phospholipid vesicles of less than 1 µm released into the blood flow by various types of cells such as endothelial, platelet, white or red blood cells. They are involved in many biological and physiological processes including hemostasis. In addition, an elevated number of microparticles in the blood is observed in various pathological situations. In the context of transfusion, erythrocyte-derived microparticles are found in red blood cell concentrates. Their role is not elucidated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 46 publications
0
56
0
Order By: Relevance
“…Most microvesicles in the systemic circulation originate from platelets [ 26 ] but they may originate from a variety of cells, including leukocytes [ 27 ], red blood cells [ 28 ] and endothelial cells [ 29 ]. As they transport substances derived from the cell of origin they may contain a broad spectrum of receptors, DNA, mRNA, micro RNA, histones and other proteins, as well as lipids capable of interacting with cells.…”
Section: Microvesiclesmentioning
confidence: 99%
“…Most microvesicles in the systemic circulation originate from platelets [ 26 ] but they may originate from a variety of cells, including leukocytes [ 27 ], red blood cells [ 28 ] and endothelial cells [ 29 ]. As they transport substances derived from the cell of origin they may contain a broad spectrum of receptors, DNA, mRNA, micro RNA, histones and other proteins, as well as lipids capable of interacting with cells.…”
Section: Microvesiclesmentioning
confidence: 99%
“…1823 MP release from platelets,24 red blood cells,25 endothelial cells, tumor cells,26,27 and leucocytes28 has been reported. Because MPs are shed membrane vesicles, the antigens expressed on the original cells are expressed on the membrane of the MPs.…”
Section: Mpsmentioning
confidence: 98%
“…Most studies have shown that microparticles are heterogeneous and vary in phospholipids, surface antigens, and protein contents. MP release is a controlled process triggered by various stimuli including proapoptotic stimulation, shear stress, agonists, or damage [6]. By general consensus, MPs are small in size, expose the anionic phospholipid (PL) phosphatidylserine (PS) on the outer leaflet of their membrane, and bear surface membrane antigens reflecting their cell of origin [7].…”
Section: Microparticlesmentioning
confidence: 99%